Тhermodynamic analysis of magnesiothermy in a salt melt during titanium production - Kolbin , M.O.; Ihnatiev , V.S.; Holovachоv A.M.; Yaroshenko , Ya.O.; Losev , R.R. (Theory and Practice of Metallurgy, 2023)
The purpose of this work is to calculate, using the HSC program, the change in the thermal effect of the reaction and the free energy of magnesiothermal reduction in a salt melt during titanium production. The results show that the change in the thermal effect of the double-salt reaction is about 4 times less than the traditional Kroll method. Thus, the results allow us to recommend this double salt (TiCl2 - MgCl2) as a reagent for the production of titanium by the magnesiothermal method